Customer Attitude Towards Car Sharing, Electric Vehicles and Autonomous Driving: Evidence from Indonesia (Journal of Asian Development Studies, 2025)
Electric vehicle (EV) and autonomous vehicle (AV) technologies have made significant strides and are anticipated to play a substantial part in the future transportation system. Little research has concentrated on the public's perception of autonomous electric cars (AEVs), while some has examined the potential effects of AEVs. This research employs the Technology Acceptance Model to investigate the general public's perceptions of AEVs. This study examines the impact of environmental concern on people's perceptions of AEVs, taking into account the potential environmental benefits of AEVs. An online survey in Indonesia was used to gather the information, which was then analysed using a structural model. Data was collected from the car and heavy bikes community of 370 customers. The findings indicate that people's intentions to use AEVs are positively related to their perceptions of green perceived usefulness, perceived ease of use, and environmental concern. Environmental concerns, mediated by various factors, have a significant indirect effect on usage intention. The research presents an in-depth framework for analysing consumer attitudes toward autonomous electric vehicles and environmental concerns. The study also recommends a future research agenda in the domains of consumer electric car and car sharing, which relate to social class and gender.